Uso de herramientas tecnológicas y lectoescritura en estudiantes del cuarto grado de educación primaria de la Institución Educativa N° 601324 Virgen de las Mercedes, San Juan Bautista 2022 - Rengifo Panduro, Estephannie Elizabeth (2023)
The study is based on the following main question and objective: What is the relationship between the use of technological tools and literacy in students of the fourth grade of primary education of the Educational Institution No. 601324 Virgen de las Mercedes San Juan Bautista? 2022? and relate the use of technological tools and literacy in the students of the educational institution. The design and type of research considered were field, cross-sectional, bivariate, and relational, respectively. The subjects of the study as population and sample were 131 students. To record the data, questionnaires were used through the survey technique, prior to the application of these they went through a process of validation by experts. Conclusion: That, the statistical value of Student's t = 5.166; p-value (bilateral significance) = 0.000, with a probability of error of 0.00%, and with a significance level of 5%, allow us to affirm that there is a significant association between the variables investigated, which demonstrates the hypothesis: The use of the technological tools is related to the literacy of primary school students in the Educational Institution No. 601324 Virgen de las Mercedes San Juan Bautista 2022.